Specialized pro-resolving mediator 7S MaR1 inhibits IL-6 expression via modulating ROS/p38/ERK/NF-κB pathways in PM 10 -exposed keratinocytes - Jinju Kim; Hyo-min Park; Chae-min Lim; Kyeong-bae Jeon; Seonhwa Kim; Jin Lee; Jin-tae Hong; Deok-kun Oh; Young Yang; Do-young Yoon (BMB reports, 2024)
Keratinocytes are susceptible to airborne particulate matter (PM) exposure, resulting in human skin barrier dysfunction. Therefore, it is important to find useful reagents to resolve skin damages caused by PM. Here, we explored the protective effect of 7S MaR1, a specialized pro-resolving mediator derived from docosahexaenoic acid, on skin inflammation and the oxidative stress induced by PM with a diameter 10 μm or less (PM 10 ) in human keratinocyte HaCaT cells. Interestingly, PM 10 -induced ROS generation was modulated by 7S MaR1 via the recovery of ROS scavenger genes. 7S MaR1 reduced PM 10 -induced IL-6 expression via modulating the p38/ERK/NF-κB signaling pathways. These results demonstrate that PM 10 induces inflammatory cytokines, which can lead to skin diseases. In addition, 7S MaR1 can resolve inflammation caused by PM 10 -induced oxidative stress and inflammatory cytokines. [BMB Reports 2024; 57(11): 490-496]